2020
DOI: 10.1084/jem.20200483
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of germinal-center B cells informs on lymphoma cell of origin and outcome

Abstract: In response to T cell–dependent antigens, mature B cells are stimulated to form germinal centers (GCs), the sites of B cell affinity maturation and the cell of origin (COO) of most B cell lymphomas. To explore the dynamics of GC B cell development beyond the known dark zone and light zone compartments, we performed single-cell (sc) transcriptomic analysis on human GC B cells and identified multiple functionally linked subpopulations, including the distinct precursors of memory B cells and plasma cells. The gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
185
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(223 citation statements)
references
References 70 publications
(119 reference statements)
21
185
0
Order By: Relevance
“…Although ASC. 23 Consistent with other scRNA profiling of GC B cell populations, 113,114 we observed substantial heterogeneity within the activated, dividing B cell population. 23 One scRNA-seq analytical approach is to take advantage of the heterogeneity and small differences between cells to order cells along a response trajectory termed pseudotime.…”
Section: When Is Plasma Cell Fate Imprinted?supporting
confidence: 89%
“…Although ASC. 23 Consistent with other scRNA profiling of GC B cell populations, 113,114 we observed substantial heterogeneity within the activated, dividing B cell population. 23 One scRNA-seq analytical approach is to take advantage of the heterogeneity and small differences between cells to order cells along a response trajectory termed pseudotime.…”
Section: When Is Plasma Cell Fate Imprinted?supporting
confidence: 89%
“…Data can be processed with dedicated software, such as Single-Cell_Signature_Explorer and single cell virtual cytometer, the first published method for qualitative and scoring of single gene or gene-set based signatures (68). This method could thus provide informations about: cellular heterogeneity and evolution (our data, in press), clues of cell maturation through pseudo-temporal trajectory analysis (74) or cellular dynamics by RNA velocity determination (70), or definition of GC differentiation state based on CXCR4 and CD86 proteins expression levels, thus confirming sc transcriptomics data (20).…”
Section: Upcoming Improvement To Unravel Tme From Scrna-seq Approachessupporting
confidence: 73%
“…Sample origin was a major source of genetic heterogeneity across the 5 FL patients, but intra-patient heterogeneity was not linked to subclonal genomic diversity, since IGH subclones tracking found that a given subclone could be found in different states (at least in the 91-gene panel). A second study ( 20 ) applied scRNA profiling to dissect the heterogeneity of GC tumors cell-of-origin (sc-COO). Given inter-donor consistency, in terms of gene signature associated to specific subsets of GC cells, they identified multiple functionally linked subpopulations (with some cells showing intermediate level of GC differentiation process between DZ/LZ), as well as the precursors of both memory B cells and antibody secreting cells (based on expression of CCR6 and PRDM1 ).…”
Section: Applications Of Scrna-seq: In Search Of the Cell Of Origin Amentioning
confidence: 99%
“…Furthermore, there is an unmet need to translate theoretical information into clinical practice which has been done, for example, with the use of adavosertib, an WEE1 inhibitor, to increase response in DLBCL patients. In line with this, the incorporation of single-cell sequencing technology can help identify B-cell stages (dark/light zone) and cell cycle phases to further amplify the possibilities for therapy options [ 17 , 46 , 83 ].…”
Section: Resultsmentioning
confidence: 99%